Investigation on the thermal properties of new thermo-reversible networks based on poly(vinyl furfural) and multifunctional maleimide compounds - C. Gaina; O. Ursache; V. Gaina; E. Buruiana; D. Ionita (eXPRESS Polymer Letters, 2012)
New thermo-reversible networks were obtained from poly(vinyl furfural) and multifunctional maleimide monomers by Diels-Alder (DA) and retro-DA reactions. The poly(vinyl furfural) having acetalization degree of 15 and 25% were obtained by the acid-catalyzed homogenous acetalization of poly(vinyl alcohol) with 2-furfural in a nonaqueous media. The thermal and viscoelastic behaviour of the cross-linked materials have been studied via differential scanning calorimetry, dynamic mechanical analysis and thermogravimetric analysis. The networks exhibit considerable swelling in those organic solvents that dissolve both poly(vinyl furfural) and bismaleimides; by heating in aprotic dipolar solvents at 150°C, they become soluble.